2009
DOI: 10.1002/chem.200901322
|View full text |Cite
|
Sign up to set email alerts
|

Vinylation of Nitro‐Substituted Indoles, Quinolinones, and Anilides with Grignard Reagents

Abstract: The reaction of vinyl Grignard reagents with o-methoxynitroarenes containing an electron-releasing substituent para to the nitro group proceeds through a pathway that is different from the initially expected Bartoli indole synthesis. Thus, instead of giving fused indole derivatives, these reactions provide a very mild and efficient new procedure for the synthesis of synthetically relevant aromatic systems containing an o-nitrovinyl moiety, such as 5-nitro-4-vinylindoles, 6-nitro-7-vinylindoles, 6-nitro-5-vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…70,71 Considering the high stabilization of dinitrobenzene radical anions, 72 the occurrence of the reaction is quite surprising.…”
Section: Monica Nardimentioning
confidence: 98%
“…70,71 Considering the high stabilization of dinitrobenzene radical anions, 72 the occurrence of the reaction is quite surprising.…”
Section: Monica Nardimentioning
confidence: 98%
“…On the other hand, the less hindered 2‐naphthylmagnesium bromide gave a mixture of compounds 6j and 7j . It is pertinent to mention that the reaction between compound 4 and the less hindered vinylmagnesium bromides exclusively afforded 5‐vinylindoles 12. The diarylamine structure of compounds 6 was deduced from spectroscopic data and confirmed by the independent synthesis of compound 6d .…”
Section: Resultsmentioning
confidence: 88%
“…The preparation of the starting material is summarized in Scheme . Compound 3 was prepared by N ‐methylation of 5 under phase‐transfer catalysis conditions, using our previously published procedure 12. The synthesis of 4 was achieved by O ‐methylation of 5 with methyl iodide in the presence of silver oxide as the base.…”
Section: Resultsmentioning
confidence: 99%
“…Two exceptions were the hydroxycarboxylic acids 1{f} , 1{j} and the methoxycarboxylic acids 1{g} , 1{k} , which all failed in that very complex mixtures were obtained. Recently, it was reported that methoxynitroarene gave somewhat different products in the presence of Grignard reagent [48]. …”
Section: Resultsmentioning
confidence: 99%